Pengendalian Aset Nirwujud dalam Manajemen Sistem Irigasi: Konsep dan Pengembangan Model - Nugroho Tri Waskitho; Sigit Supadmo Arif; Mochammad Maksum; Sahid Susanto (agriTECH, 2013)
Irrigation was an important component of the agricultural development in Indonesia, but it had many problems. Irrigation management was inefficient, irrigation networks were damaged and farmers participation were poor. These problems were caused by poor of intangible assets. The research aimed at developing the concept and the model of controlling intangible assets in irrigation system management. The research method consisted of two stages. The first stage was developing the concept. The concept of controlling intangible assets in irrigation system management was developed based on principles of knowledge management. The concept stated that intangible assets in irrigation system can be controlled using knowledge management. The second stage was developing the model which consisted of model building and sensivity analysis. Model of controlling intangible assets in irrigation system management was build using neuro-fuzzy. The model had three submodels: knowledge management, intangible assets and performance of irrigation system. Evaluating the model was done in Sapon irrigation system in Kulon Progo, Yogyakarta. Data collecting was done using questionnaire on nine Water Use Associations. Data analysis was done using Adaptive Neuro Fuzzy Inference System. The model had been evaluated using correlation coefficient, Mean Absolute Percentage Error and Root Mean Square Error. Result of the study indicated that the concept of controlling intangible assets in irrigation system management had developed based on knowledge management. The concept stated that irrigation system management had to balance between tangible assets and intangible assets. Intangible assets which had amortization need be controlled. Controlling intangible assets can be done by knowledge management. The model of controlling intangible assets in irrigation system management could predict intangible assets and performance of irrigation system well. The model linked knowledge management, intangible assets and performance of irrigation system.  Knowledge management felt into four main components: learning organization, principle of organization, policy and strategy of organization and information and communication technology which controlling intangible assets in irrigation system. Intangible assets consisted of moral intelligence, emotional intelligence, creative attitude, institutional culture, and farmer participation which  controlling effectiveness of irrigation system. Learning organization was the most sensitive parameter in influencing moral intelligence and creative attitute.  Policy and strategy were the most sensitive parameter in influencing emotional intelligence, institutional cultura and farmer participation. Farmer participation was the most sensitive parameter in influencing effectiveness of irrigation system.ABSTRAKIrigasi merupakan komponen penting dalam pembangunan sektor pertanian di Indonesia namun masih mempunyai banyak permasalahan. Manajemen irigasi belum efisien, partisipasi petani yang menurun, jaringan irigasi yang rusak sehingga menurunkan kinerja sistem irigasi. Permasalahan tersebut disebabkan rendahnya kualitas aset nirwujud sistem irigasi. Tujuan penelitian adalah mengembangkan konsep dan model pengendalian aset nirwujud dalam manajemen sistem irigasi. Metode penelitian terdiri dari dua tahap. Tahap pertama adalah pengembangan konsep. Konsep pengendalian aset nirwujud dalam manajemen sistem irigasi dikembangkan dari prinsip manajemen pengetahuan. Tahap kedua adalah pengembangkan model yang terdiri dari pembangunan model dan analisis sensitivitas. Pembangunan model pengendalian aset nirwujud dalam manajemen sistem irigasi berbasis manajemen pengetahuan dengan prinsip neuro-fuzzy. Model mempunyai tiga submodel yaitu manajemen pengetahuan, aset nirwujud dan kinerja sistem irigasi. Pengujian model dilakukan di Daerah  Irigasi Sapon di Kabupaten Kulon Progo, Propinsi Daerah Istimewa Yogyakarta. Pengumpulan data dilakukan dengan kuesioner terhadap sembilan Perkumpulan Petani Pemakai Air. Analisa data dilakukan dengan   Adaptive Neuro Fuzzy Inference System. Model dievaluasi dengan koefisien korelasi, Mean Absolute Percentage Error dan Root Mean Square Error. Penelitian menghasilkan bahwa konsep pengendalian aset nirwujud dalam manajemen sistem irigasi telah tersusun berbasis manajemen pengetahuan. Konsep menekankan bahwa manajemen sistem irigasi harus menyeimbangkan antara aset wujud dengan aset nirwujud. Aset nirwujud yang selama ini kurang diperhatikan mengalami penyusutan sehingga perlu dikendalikan. Upaya pengendalian aset nirwujud dilakukan dengan manajemen pengetahuan. Model pengendalian aset nirwujud dalam manajemen sistem irigasi yang menggunakan prinsip neuro-fuzzy dapat memprediksi aset nirwujud dan efektivitas sistem irigasi dengan cukup memadai. Model menghubungkan manajemen pengetahuan, aset nirwujud dan kinerja sistem irigasi.  Manajemen pengetahuan yang terdiri dari organisasi pembelajar, prinsip organisasi, kebijakan dan strategi organisasi, teknologi informasi dan komunikasi mempengaruhi aset nirwujud sistem irigasi. Aset nirwujud yang terdiri dari kecerdasan moral, kecerdasan emosional, sikap kreatif, budaya lembaga, dan partisipasi petani mempengaruhi efektivitas sistem irigasi. Organisasi pembelajar merupakan parameter yang paling sensitif dalam mempengaruhi kecerdasan moral dan sikap kreatif.  Kebijakan dan strategi merupakan parameter yang paling sensitif dalam mempengaruhi kecerdasan emosional, budaya lembaga dan partisipasi petani. Partisipasi petani merupakan parameter yang paling sensitif dalam mempengaruhi efektivitas sistem irigasi.